Methods and means of monitoring the physical condition of metal structures - Запорожець, О.І.; Глива, В.А.; Клапченко, В.І.; Потапенко, Г.Д.; Лук'янчиков, А.В. (Proceedings of National Aviation University, 2007)
The method of continuous, automatic control of bodily condition of metallic constructions is developed due to registration of electric currents of source and acoustic emission in the elements of constructions. The offered method allows to accumulate, to process the registered signals and warn about their approaching to the critical levels and automatic mode.